The Future of Media Interfaces - Jorge, Joaquim (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2019: Anais Estendidos do XVIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2019.8371, 2019)
We are living in a post-WIMP world. Indeed, more and more users access information, communicate and operate mobile information appliances foregoing the still common mouse and keyboard of yonder. However, no matter how powerful or elegant the new mobile devices are, it is the user interface that ultimately governs how successful new devices or systems will be. In this lecture I will look at current multimedia systems and their applications to virtual environments and ubiquitous computing. Multimedia user interfaces currently engage people using images, video and sound but virtual environments not only involve interactive 3D graphics, but further need to take more advantage of our senses through spatial audio, haptics and many other novel and exciting communication modalities. This talk will explore key current research issues and future directions up to and before the prophesized singularity.